A clinical study of efficacy and safety of the Carry Life UF system in continuous ambulatory peritoneal dialysis patients: protocol for a prospective, multicenter, randomized, crossover study - Wilkie, Martin; de Leon, Charlotte; Carlsson, Ola; Hegbrant, Jörgen; Heimbürger, Olof (BMC nephrology, 2025)
Carry Life UF is a novel peritoneal dialysis (PD) technology for improved fluid management using steady concentration PD (SCPD). The Carry Life UF treatment starts with a manual peritoneal fill of 1.36% glucose PD fluid, followed by a 5-hour treatment where small amounts of glucose are continuously added to maintain a stable intraperitoneal glucose concentration. A recent in-center clinical study using the Carry Life UF system demonstrated higher ultrafiltration (UF) rates, more efficient use of glucose (increased UF volume/gram of glucose absorbed), and greater sodium removal with the Carry Life UF treatments compared with a 2.27% glucose continuous ambulatory PD (CAPD) dwell. The aim of this study is to compare efficacy and safety of the Carry Life UF system with a standard CAPD prescription in the home setting. A prospective, multicenter, randomized, crossover study of 19 adult subjects at up to 12 sites in Italy, Sweden and the UK will complete the investigation. End-stage kidney disease patients with a CAPD prescription of 2-4 exchanges per day, including at least one 2.27% glucose dwell, will be included. After a Carry Life UF glucose dose determination phase performed in-clinic, subjects will be randomized to start the home treatment part of the study with either the control arm (2.27% glucose CAPD dwell) or the Carry Life UF arm (11 or 15 g/h glucose dose), each for four weeks. The primary endpoint is UF volume comparing the control CAPD 2.27% glucose dwell with the Carry Life UF treatment. Secondary endpoints include adverse event rates, peritoneal sodium removal, glucose UF efficiency, and peak dialysate glucose concentration. This study will evaluate a novel PD technology in the home environment. Challenging aspects include the need to accurately measure UF volumes at home and to support subjects in using a novel technology. The study design considers important parameters for precise UF volume measurements and provides detailed weighing instructions to the study team to ensure consistency between study centers. Research nursing support will be provided for training of subjects and to support endpoint data collection in the subjects' home. Due to the significant burden associated with the study, subjects will be offered a fair compensation, in accordance with local regulations. ClinicalTrials.gov Identifier: NCT05874804 Registration date: 18th of April 2023.